The impact of anxiety on affective and cognitive empathy - Manjeet Susch; Andrew D. R. Surtees (PLoS ONE, 2025)
Existing evidence about the way anxiety impacts empathy is mixed, highlighting the complexity of empathy as a construct. The impact of state anxiety on affective and cognitive empathy in women was tested. Seventy-five women underwent an anxiety or relaxation induction, prior to completing measures of affective and cognitive empathy, and trait anxiety. Robust positive correlations were found between trait cognitive and trait affective empathy, and trait and performance affective empathy. Induced anxiety impaired affective empathy performance when controlling for trait empathy, however, was not observed to impact cognitive empathy performance. Trait anxiety and empathy did not moderate the influence of induced anxiety on affective empathy performance. Irrespective of trait levels of anxiety and empathy, women are less affectively empathic when anxious, but do not vary in their cognitive empathy.